2015
DOI: 10.14814/phy2.12483
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dehydration on muscle metabolism and time trial performance during prolonged cycling in males

Abstract: This study combined overnight fluid restriction with lack of fluid intake during prolonged cycling to determine the effects of dehydration on substrate oxidation, skeletal muscle metabolism, heat shock protein 72 (Hsp72) response, and time trial (TT) performance. Nine males cycled at ∼65% VO2peak for 90 min followed by a TT (6 kJ/kg BM) either with fluid (HYD) or without fluid (DEH). Blood samples were taken every 20 min and muscle biopsies were taken at 0, 45, and 90 min of exercise and after the TT. DEH subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 31 publications
(67 reference statements)
2
41
0
4
Order By: Relevance
“…However, this confounding effect seems unlikely given that changes in the expression of angiogenic factors and heat shock proteins were remarkably similar between the LBH and TH protocols (Table 7), even though there is negligible dehydration during localized limb heating. In addition, Logan-Sprenger et al (35) recently reported that mild dehydration induced by overnight fluid restriction had no significant impact on the expression of HSP72 in skeletal muscle in humans. Taken together, these observations indicate that mild dehydration does not seem to impact the expression of angiogenic factors and heat shock proteins in skeletal muscle.…”
Section: Limitationsmentioning
confidence: 99%
“…However, this confounding effect seems unlikely given that changes in the expression of angiogenic factors and heat shock proteins were remarkably similar between the LBH and TH protocols (Table 7), even though there is negligible dehydration during localized limb heating. In addition, Logan-Sprenger et al (35) recently reported that mild dehydration induced by overnight fluid restriction had no significant impact on the expression of HSP72 in skeletal muscle in humans. Taken together, these observations indicate that mild dehydration does not seem to impact the expression of angiogenic factors and heat shock proteins in skeletal muscle.…”
Section: Limitationsmentioning
confidence: 99%
“…Proper daily consumption of fluids, principally water, should be encouraged for its health benefits. In general, dehydration may affect the rate of glucose oxidation and glycogen metabolism, increasing carbohydrate needs and potentially increasing the risk of hypoglycaemia [24-27] in individuals with type 1 diabetes. Moreover, low total water intake in people with T2DM acutely impairs blood glucose response during an oral glucose tolerance test [28].…”
Section: Discussionmentioning
confidence: 99%
“…Rozvíjí se absolutní hypovolemie (pokles plasmatického objemu) zvyšující nároky na srdeční výdej s následnou kompenzací vyšší srdeční frekvencí a relativní hypovolemie (snížení průtoku krve podkožím). Výsledkem zhoršené schopnosti organizmu eliminovat produkované teplo je riziko vzestupu tělesné teploty (teploty jádra), zvýšení hladin katecholaminů a akcentovaná glykogenolýza přispívající k dřívějšímu rozvoji únavy u vytrvalostního zatížení (Logan-Sprenger, Heigenhauser, Jones, & Spriet, 2015). Hypohydratace snižuje výkon, přesáhne-li teplota pokožky 27 °C, a s každým dalším stupněm navíc dochází k poklesu výkonu o 1,5 % (Sawka, Cheuvront, & Kenefick, 2015).…”
Section: Dehydratace a Sportovní Výkonunclassified